A reconfigurable transmitarray unit cell employing liquid metal - Zhishu Qu; Yihua Zhou; James R. Kelly; Zhengpeng Wang; Kenneth Lee Ford; Yue Gao (IET Microwaves, Antennas & Propagation)
Abstract In this paper, a reconfigurable transmitarray unit cell using liquid metal is presented. It consists of three conducting layers where the geometries of the resonators, on the different layers, differ and consist of an arrow shape together with rotated split rings. The arrow‐shaped conducting layer has the capability to convert the polarization of the incoming waves by 90°. The split ring resonators, on the upper and lower conducting layers, have the same dimensions but different orientations (horizontal and vertical polarization). Several fluidic channels are placed beneath/above the conducting layers. The transmission behaviour of the unit cell can be changed by altering the geometrical parameters which is achieved by injecting the liquid metal into the channels. More than 300° phase shift range with a maximum S21 of ∼ −1.5 dB at 3.3 GHz is obtained. It exhibits 3 dB of insertion loss over a bandwidth ranging from 3.2 to 3.43 GHz. It is the first time that a transmitarray unit cell, reconfigured employing liquid metal, provides a combination of low insertion loss and large phase shift range. The proposed prototype was fabricated and measured within an open‐ended waveguide and the measured results agree well with the simulations and verify the effectiveness of the design. The reconfigurable transmitarray unit cell can be used to design beam‐scanning arrays, as well as for applications in wireless communications.